Attitude Towards Advertising: A Young Generation Cohort's Perspective - Hiram, Ting; Ernest Cyril, de Run (Asian Journal of Business Research, 2015)
This study aims to investigate young consumers’ views about advertising from generation perspective. Specifically, it seeks to scrutinize the effects of both advertising beliefs and personal values on their attitude towards advertising. As past studies review little about the implication of generation on advertising attitude in developing markets, the study looks into the subject matter from the standpoint of a young generation cohort in Sarawak. Self-administered survey was utilized on the basis of purposive sampling strategy to sample Neoteric-inheritors (aged 15-21 as of 2013) in the state. 450 copies of questionnaire were distributed, and 384 usable copies were subsequently collected. Data was analyzed using descriptive analysis and regressions. The findings show that product information, social role/image, being good for the economy, not being materialistic and truthfulness have significant effect on Neoteric-inheritors’ attitude towards advertising. Contrary to past studies, their advertising attitude is found to be predominantly formed by positive beliefs. Moreover, only internal value is found to be significant in predicting attitude though the effect is weak. The study thus provides insights into how young consumers in developing markets view advertising, and how the understanding of generation articulates the effect of advertising beliefs and personal values on attitude and behavioural intention. By understanding the embedded orientations in generation, knowledge about young consumers’ attitude towards advertising, and advertising effectiveness can be further enhanced.